(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Alcohol consumption is a well-known public health problem, especially among university students. It was poorly studied in Middle East, especially in Iraq, due to religious and social taboos. This study conducted to throw a light on the prevalence of Alcohol consumption among university students in Baghdad. Subjects and methods: A survey conducted in three universities (Baghdad, Al-Mustansiriyah and Al-Nahrain) from Baghdad city, in the duration between January and May 2015.A semi-structured questionnaire form used to collect the data from 1435 university students. The sample selected by multistage random sampling technique with probability proportion to size. Results: The average age (range) of the studied sample was 19.8 (18 - 24) years; more than a half of them were females 760 (53%). Alcohol consumption was reported by 9.7% (95%CI: 8.2% - 11.2%) of the participants (19.7% males vs. 0.8% females). Heavy Alcohol consumption was reported by 12.2% of consumers. Male students living out of their families or relatives and those of medical group colleges found to be risk factors for Alcohol consumption (PR= 2.65, 95% CI: 1.72 - 4.1) and (PR= 2.72, 95%CI: 1.48 - 5.01) respectively. No significant relations showed between demographic characters of female students and Alcohol consumption. Conclusions: Usage of Alcohol was relatively prevalent among university students in Baghdad, in spite of religious and social barriers in Iraq. Family and college staff supervision and education of the students with meetings targeting health risks and sequels of Alcohol hazardous consumption are the effective ways to control this practice.